Identification of a suitable working posture for female workers engaged in golden thread work - Payel Maity; Sujaya De; Amitava Pal; Hiranmoy Mahata; Mousumi Chatterjee; Prakash C. Dhara (Occupational Health and Safety Society of Nepal, 2016)
Background: The golden thread (jori) work is one of the major home based industries providing employment to thousands of artisans spread over several rural areas of the West Bengal. The study is essentially labor intensive and thus workers are prone to suffer from work related health problems. Objective: The present study was aimed to evaluate the musculoskeletal disorders (MSDs) and postural stress of the female golden thread workers. Methods: The study was carried on 123 adult female golden thread workers in different districts of West Bengal. The prevalence of MSD, body part discomfort rating (BPD) and postural stress (by OWAS, RULA, REBA method) of the workers were evaluated by standard methods. The EMG of shoulder and back muscle was recorded with the help of the BIOPAC system. Result: The results showed that the prevalence of MSDs, BPD rating and postural stress were comparatively lower in case of sitting on the floor with folded legs than squatting and sitting on the floor with stretched legs. The EMG and RMS values of EMG voltage of shoulder and back muscle were comparatively lower in this posture than that of other two postures. Conclusion: It was therefore, concluded that sitting on the floor with folded legs was less hazardous and it imposed less postural stress in comparison to other sitting postures adopted by the golden thread workers. International Journal of Occupational Safety and Health, Vol 4 No 2 (2014) 24 - 33